2008
DOI: 10.1089/cap.2007.0084
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Pharmacokinetic, Safety, and Tolerability Profiles of Quetiapine, Norquetiapine, and Other Quetiapine Metabolites in Pediatric and Adult Patients with Psychotic Disorders

Abstract: Pediatric and adult populations demonstrated similar pharmacokinetic, safety, and tolerability profiles for quetiapine administered by dose escalation. The predictability in quetiapine concentration profiles for children aged 10 years to adults suggests that no dosage adjustment may be required when treating patients of these ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 26 publications
3
34
1
Order By: Relevance
“…For example, active metabolites of clozapine (Burstein et al, 2005) and quetiapine (Jensen et al, 2008;Winter et al, 2008) have been reported to have unique profiles differing from that of their mother compounds. A recent report showed that a metabolite of quetiapine (N-desalkylquetiapine) is capable of inhibiting norepinephrine uptake, suggesting that the antidepressant effect of quetiapine in bipolar depression is at least partially mediated by the potent antidepressant activity of N-desalkylquetiapine (Jensen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, active metabolites of clozapine (Burstein et al, 2005) and quetiapine (Jensen et al, 2008;Winter et al, 2008) have been reported to have unique profiles differing from that of their mother compounds. A recent report showed that a metabolite of quetiapine (N-desalkylquetiapine) is capable of inhibiting norepinephrine uptake, suggesting that the antidepressant effect of quetiapine in bipolar depression is at least partially mediated by the potent antidepressant activity of N-desalkylquetiapine (Jensen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we have been unable to measure this metabolite. According to a pharmacokinetic study (Winter et al 2008) expected plasma concentrations of N-desalkylquetiapine under steady-state conditions attain about 25 % of those of the mother compound 2 h after drug intake, and metabolite concentrations are about 1.8-fold higher than those of quetiapine at the end of the dosing interval (trough concentrations). Consideration of this compound would probably result in better correlations between active moiety concentrations and receptor occupancies.…”
Section: Plasma Level Vs D 2/3 R Occupancy Relationshipmentioning
confidence: 99%
“…The pharmacokinetics of immediate release (IR) and extended release (XR) quetiapine fumarate and several metabolites have been characterized previously [25,26]. To demonstrate the utility of this methodology for the measurement of quetiapine and its four metabolites in human plasma, the plasma concentration-time profiles shown in Fig.…”
Section: Cross-validation Studymentioning
confidence: 99%